2021
DOI: 10.1016/j.yjmcc.2021.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Translational investigation of electrophysiology in hypertrophic cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) patients are at increased risk of ventricular arrhythmias and sudden cardiac death, which can occur even in the absence of structural changes of the heart. HCM mouse models suggest mutations in myofilament components to affect Ca 2+ homeostasis and thereby favor arrhythmia development. Additionally, some of them show indications of pro-arrhythmic changes in cardiac electrophysiology. In this study, we explored arrhythmia mechanisms in mice carrying a HCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 66 publications
3
11
0
Order By: Relevance
“…The same pattern of decreased K + channel expression was observed in several transgenic mouse models of HCM carrying different mutations [28][29][30]56]. Toib and colleagues, in a HCM transgenic rodent model with MyBPC knockout (KO), demonstrated that a reduction of K + currents resulted in a significant prolongation of the QT interval at the ECG evaluation and premature ventricular contractions (PVCs) evidenced by telemetry recordings [28].…”
Section: Timeline Of Ion Current Remodeling In Hcmmentioning
confidence: 63%
See 3 more Smart Citations
“…The same pattern of decreased K + channel expression was observed in several transgenic mouse models of HCM carrying different mutations [28][29][30]56]. Toib and colleagues, in a HCM transgenic rodent model with MyBPC knockout (KO), demonstrated that a reduction of K + currents resulted in a significant prolongation of the QT interval at the ECG evaluation and premature ventricular contractions (PVCs) evidenced by telemetry recordings [28].…”
Section: Timeline Of Ion Current Remodeling In Hcmmentioning
confidence: 63%
“…Measurements with sharp microelectrodes in the LV endocardium revealed that hearts from homozygous mutant mice were characterized by significantly longer APs compared to heterozygous mutant mice and WT mice, both in postnatal day 1 and 30-week-old mice, confirming that: 1) AP prolongation represents one of the main EP abnormalities of HCM and 2) the electrical impairment typical of HCM occurs early during the pathological phenotype development. Interestingly, all outward currents were reduced in aged homozygous mice compared to WT animals and this decrease was particularly evident for I to and I Ks [29]. The reliability of these measurements was confirmed by incorporating all the data related to K + and Ca 2+ currents in a computational model of a mouse ventricular AP: the "in silico" representation resulted in a similar prolongation of APD in computed homozygous MYBPC3 mutant cells, as compared to WT myocytes [29].…”
Section: Animal Modelsmentioning
confidence: 67%
See 2 more Smart Citations
“…After demonstrating the efficacy with diltiazem in EHTs, the drug improved the electrical phenotype of HCM-affected family members. Flenner et al generated hiPSCs with an HCM mutation (homozygous MYBPC3 mutant; MYBPC3hom) and the hiPSC-CM-derived EHTs harboring this mutation exhibited lower K + current protein levels, force, beating frequency, and relaxation time, highlighting the application of not only force measurements but also arrhythmia susceptibility ( Flenner et al, 2021 ). Tsan et al generated micron-scale cardiac muscle bundles from hiPSC-CMs with a deletion of the MYBPC3 promoter, and demonstrated that contractile velocities were higher while relaxation velocities were lower, recapitulating the kinetics of HCM ( Tsan et al, 2021 ).…”
Section: Patient-specific Ipsc-cms As Disease Modelsmentioning
confidence: 99%